Clinical and neuropsychological features associated with progression in subjective cognitive decline - Villino-Rodríguez, Rafael; Ríos-Rivera, Mirla M.; Montoya-Murillo, Genoveva; Patricio Baldera, Jonathan; Salazar-Londoño, Salomón; Rodríguez-Oroz, María Cruz; Borda, Miguel Germán; Jiménez-Huete, Adolfo; Riverol, Mario (Frontiers in Aging Neuroscience, 2025)
Background and objectivesSubjective Cognitive Decline (SCD) is recognized as an early indicator of neurodegeneration, yet factors that predict its progression to mild cognitive impairment (MCI) or dementia remains not fully understood. In this study, we aim to identify clinical and neuropsychological features associated with the progression of SCD.Methods450 persons with SCD were included, consisting in 319 non progressors (SCDnp) and 131 progressors (SCDp) to MCI or dementia due to AD. The study was conducted at the Clínica Universidad de Navarra Memory Clinic between 2001 and 2017. We included data on medical interviews and neuropsychological evaluations. Differences between SCDnp and SCDp were assessed and, to evaluate the association between exposure variables and progression in time, proportional-hazards Cox models were applied. In addition to the exposure variables, the models were adjusted for age, sex, and years of education.ResultsAt baseline, SCDp were older, had a higher prevalence of hypertension and hypercholesterolemia and had worst performance on tests related to processing speed, verbal fluency, visual memory, verbal memory, and executive functioning. Factors associated with progression at follow-up were lower scores in some cognitive tests: MMSE, TMT-B, and the CERAD regarding trial 1 of immediate recall, trial 2 of immediate recall, trial 3 of immediate recall and the delay recall score.DiscussionLower scores on global cognition, executive functioning and verbal memory tests were predictors of progression to MCI or dementia in patients with SCD. These findings underscore the importance of nuances in neuropsychological evaluation, even with a normal score, for detecting high-risk individuals for early intervention.